Evaluation of Reporting Quality in Randomised Controlled Trials of Acupuncture for Acute Herpes Zoster by the CONSORT Statement and STRICTA Guidelines. (18th February 2020) - Qian, Guifeng; Zeng, Jingchun; Lu, Liming; Pei, Wenya; Liu, Kun; Luo, Zhenke; She, Yalin; Zhang, Pande; Lin, Guohua
Abstract : Objective . To explore the methods for improving the reporting quality of randomised controlled trials (RCTs) on acupuncture through evaluating the reporting quality in RCTs of acupuncture for acute herpes zoster by the CONSORT statement and STRICTA guidelines. Methods . English and Chinese databases were searched from database creation until October 2018 and updated to July 2019. The basic characteristics and methodological quality of the literatures included were evaluated based on the CONSORT statement and the STRICTA guidelines. Descriptive statistical analysis was used in this study. The agreement between the two researchers of all items was calculated by Cohen's kappa statistics. Results . A total of 40 RCTs were included. Based on the CONSORT statement, items "Background, " "Randomised" in the title or abstract, " "Statistical methods, " and "Outcomes and estimation" were good reporting, with positive rates >80%. However, the quality of reporting in items "Sample size, " "Allocation concealment, " "Implementation, " "Blinding, " "Flow chart, " "Intent-to-treat analysis, " "Ancillary analyses, " and "Clinical Trials Register" was very poor, with positive rates <10%. Based on the STRICTA guidelines, good reporting existed in items "Acupuncture rational, " "Points used, " "Needle stimulation, " "Needle retention time, " "Course of treatment, " "Control intervention, " and "Treatment frequency, " with positive ratings >80%. The reporting quality of items "Numbers of needles inserted, " "Depth of insertion, " "Responses elicited, " and "Practitioner background" was lower, with positive rates <50%. The agreement of most items was judged as moderate, substantial, or good. Conclusion . The reporting quality of RCTs in acupuncture for acute HZ is generally inadequate. It is necessary that researchers and journal editors learn and raise the adoption of the CONSORT statement and STRICTA guidelines to enhance the reporting quality of the RCTs in acupuncture.